PENGARUH KECEMASAN DALAM MENGHADAPI UJIAN LURING TERHADAP HASIL BELAJAR BAHASA MANDARIN PADA MAHASISWA - Malahayati Hazimah; Abigail Theodora Tanzil; Jacqline Yoe (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Entering the post-pandemic period, the Indonesian education system has gradually shifted from online learning back to face-to-face instruction. This transition requires students to readjust to in-person learning in terms of academic readiness, time management, learning concentration, social interaction, and assessment demands. The adaptation process often presents various challenges, including decreased learning comfort, physical fatigue, difficulties in understanding instructional materials delivered directly, and increased psychological pressure in the form of academic anxiety. One of the most prominent sources of anxiety is examinations, which play a crucial role in evaluating learning outcomes and the overall quality of the teaching and learning process. This study aims to examine students’ anxiety levels during the transition of Mandarin language learning from online to offline modes, particularly in the context of face-to-face examinations, to compare students’ learning outcomes in online and offline examinations, and to analyze the effect of anxiety levels on learning outcomes. The findings reveal that anxiety has a significant effect on students’ academic performance. In addition, differences in anxiety levels and learning outcomes were identified between online and offline examinations, with the majority of students experiencing higher anxiety during offline examinations. This increase is influenced by learning environment conditions, social interaction, and time pressure during examinations. The results of this study are expected to contribute to educators’ understanding of offline Mandarin language learning dynamics, thereby enabling the development of more adaptive instructional and assessment strategies to enhance the quality of Mandarin language education in Indonesia. ABSTRAKMemasuki periode pascapandemi, sistem pendidikan di Indonesia mengalami penyesuaian kembali dari pembelajaran daring menuju pembelajaran luring secara bertahap. Perubahan ini menuntut mahasiswa untuk menyesuaikan diri dengan pembelajaran tatap muka, baik dari aspek kesiapan akademik, pengelolaan waktu, konsentrasi belajar, interaksi sosial, maupun tuntutan evaluasi pembelajaran. Proses adaptasi tersebut kerap memunculkan berbagai tantangan, seperti menurunnya kenyamanan belajar, kelelahan fisik, kesulitan memahami materi secara langsung, serta meningkatnya tekanan psikologis berupa kecemasan akademik. Salah satu sumber kecemasan yang dominan adalah ujian, sebagai bentuk evaluasi pembelajaran yang berperan penting dalam mengukur capaian dan kualitas proses belajar mengajar. Penelitian ini bertujuan untuk mengkaji tingkat kecemasan mahasiswa dalam menghadapi transisi pembelajaran bahasa Mandarin dari daring ke luring, khususnya pada pelaksanaan ujian luring, membandingkan hasil belajar mahasiswa Program Studi Bahasa Mandarin Universitas X pada ujian daring dan luring, serta menganalisis pengaruh tingkat kecemasan terhadap hasil belajar. Hasil penelitian menunjukkan bahwa kecemasan memiliki pengaruh yang signifikan terhadap hasil belajar mahasiswa. Selain itu, ditemukan perbedaan tingkat kecemasan dan capaian hasil belajar antara ujian daring dan luring, di mana sebagian besar mahasiswa mengalami peningkatan kecemasan saat mengikuti ujian luring. Peningkatan tersebut dipengaruhi oleh faktor lingkungan belajar, interaksi sosial, serta tekanan waktu selama ujian. Penelitian ini diharapkan dapat memberikan kontribusi bagi pengajar dalam memahami dinamika pembelajaran bahasa Mandarin secara luring sehingga strategi pembelajaran dan evaluasi dapat disesuaikan untuk meningkatkan kualitas pembelajaran bahasa Mandarin di Indonesia.